The Theory of Cultural Lag: Social Science and Its Audience in the Works of Thorstein Veblen and William F. Ogburn - Balon, Jan (Teorie vědy / Theory of Science, 2017)
The article analyses the theories of cultural lag elaborated by Thorstein Veblen and William F. Ogburn. In particular, it pursues two motives: how the relation between social science and its audience had been implied in their respective approaches, and how the “lag” argument had been employed in their view of the “purpose” of social science. It is demonstrated here that the essentially identical theory had been transformed in their “argumentative strategies” and “styles of writing” to fit their distinctive (critical and instrumental) concepts of social science. Veblen’s key motif of “self-confrontation” of society is contrasted with Ogburn’s motif of “applicability” of knowledge with regard to reflections on literary technologies of science.